TRADISI SEDEKAH BUMI DALAM UPAYA PELESTARIAN BUDAYA JAWA DI BERBAGAI DAERAH; BLORA, JEPARA, BREBES, KENDAL - Cahyani, Rizky; Utami, Nadifa Rizki; Ratnasari, Eudia Dwi; Firmansyah, Khairul; Syah, Nur Alam (Pena Edukasia, 2024)
Edupreneur adalah individu yang memadukan konsep kewirausahaan “Sedekah Bumi” is a tradition carried out and preserved by the Javanese people. Sedekah Bumi means cursing the earth as an expression of gratitude for the abundant harvest. This article reveals differences in the implementation of the earth alms tradition in several regions in Central Java. This research uses interview methods and also literature study. The library research method is a method of collecting data by searching for sources and constructing them from various sources such as journals and existing research. The purpose of the earth almsgiving is to express gratitude to Allah SWT for the blessings given to the community by abundant harvests and to honor the ancestors who have been instrumental in clearing land (tripe alas) as a place to live and a place to find life. Then, the existence of earth alms can also strengthen solidarity between communities. The results of this research show that the earth almsgiving tradition is still routinely carried out every year until now, earth almsgiving is usually held after the harvest period.